Somaclones of mandacaru (Cactaceae) with high morphological divergence may generate new varieties of ornamental cacti - Martin, Paula Garcia; Faria-Tavares, Juliana Sala; Mangolin, Claudete Aparecida; Machado, Maria de Fátima Pires da Silva (Ornamental Horticulture, 2018)
Somaclones of mandacaru cactus (Cereus peruvianus Mill.) with typical and atypical shoots were regenerated from a callus. Since the genetic relationship among regenerated somaclones has not been investigated, current study employed heterologous microsatellite primers to examine the molecular diversity within and among somaclones, showing typical and atypical phenotypes with high morphological divergence. Nei identity value calculated between the somaclones was high (I = 0.929) and AMOVA showed higher genetic variation within (96%) than among (4%) the samples of somaclones. The polymorphism in the microsatellite loci indicated high levels of mean observed and expected heterozygosity in atypical somaclones, presumably with high adaptive potential and as source of genotypes for generation of new varieties of ornamental cacti. On the other hand, low molecular divergence between typical and atypical morphologies of somaclones is a promising perspective for use of the atypical somaclones as source of chemical compounds of commercial and industrial interest. The somaclonal variations occurring in vitro callus culture has generated phenotypically differentiated subpopulations with low molecular divergence, however with high genetic variability, enough to be recommended as a source of genotypes to generate new varieties of ornamental cacti and of plants with new traits, necessary for breeding programs.